Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 6 - Logarithmic Functions - 6.1 Functions and Their Inverses - 6.1 Exercises: 44

Answer

$f^{-1}(x) = \frac{x-3.6}{0.6}$

Work Step by Step

$f(x) = 0.6x + 3.6$ Let $f(x) = y$: $y = 0.6x + 3.6$. Switch the variables $x$ and $y$ to find the inverse and solve for $y$: $x = 0.6y + 3.6$ $x - 3.6 = 0.6y$ $y = \frac{x-3.6}{0.6}$ $f^{-1}(x) = \frac{x-3.6}{0.6}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.